The Potential of Swiftlet Bird's Nest Extract (Aerodramus fucipaghus) as an Antioxidant and Serum Formulation - Widyaningrum, Naniek; Putri, Chintiana Nindya; Arief, Thendi Abdul; Sofa, Nada Aini; Virdaus, Monica (Universitas Ahmad Dahlan, 2024)
The white swiftlet bird's nest (Aerodramus fucipaghus) constitutes one of nature's treasures endowed with diverse health benefits. The swiftlet bird's nest is a potential source of antioxidants, capable of counteracting free radicals contributing to premature ageing. It can be harnessed as a serum formulation featuring small molecules, facilitating deeper skin penetration, efficient delivery of highly concentrated active agents, and expedited resolution of skin issues. This study aimed to ascertain the swiftlet bird's nest serum's physical properties, physical stability, and antioxidant activities. Serum formulations span a range of concentrations: 10%, 20%, 30%, and 40%. Physical attributes of the serum, including organoleptic properties, homogeneity, pH, spreadability, and viscosity, were observed. Serum stability was assessed over a 21-day storage period. The antioxidant activity of the serum was gauged via DPPH assay, determining the IC50 values. The serum, across varying concentrations, exhibited commendable physical characteristics, satisfying stipulated criteria. Antioxidant activity was detected in the serum across a spectrum of concentrations, revealing IC50 values of 250.00 µg/mL, signifying a range from weak to strong efficacy (90.137 µg/mL). The swiftlet bird's nest serum with its concentration variants demonstrated physical stability during the 21-day storage duration. Drawing from the research, it can be deduced that the swiftlet bird's nest holds promise for development into a serum formulation that fulfils both physical and stability criteria, endowed with robust antioxidant activity. Notably, the swiftlet bird's nest serum at a 40% concentration exhibited potent antioxidant activity, manifesting an IC50 value of 90.137 µg/mL